Comparison of Financial Performance in Pharmaceutical Industry Companies - Wahida Basri, Nur; Rum, Muh; Rustam, Andi (Manunggal Halim Jaya, 2024)
This research aims to evaluate the financial performance of PT Kimia Farma (Persero) Tbk, PT Indofarma (Persero) Tbk, and PT Kalbe Farma (Persero) Tbk during the 2016-2022 period using liquidity, profitability, leverage, activity, and efficiency ratios as comparison metrics. The research applies quantitative descriptive analysis through ratio calculations, and is classified as explanatory research with a quantitative approach. The DuPont System Analysis, which highlights the Net Profit Margin, is also employed. The findings reveal that PT Kalbe Farma (Persero) Tbk and PT Kimia Farma (Persero) Tbk showed improved financial performance in 2016-2022, characterized by an increasing liquidity ratio, indicating better debt management. In contrast, PT Indofarma (Persero) Tbk experienced a decline in its liquidity ratio, signifying poorer debt management. Additionally, all three companies—PT Kalbe Farma (Persero) Tbk, PT Indofarma (Persero) Tbk, and PT Kimia Farma (Persero) Tbk—saw declining profitability ratios during this period, reflecting lower profits, which can be considered unfavorable. Overall, while PT Kalbe Farma (Persero) Tbk and PT Kimia Farma (Persero) Tbk had relatively stable financial performance, PT Indofarma (Persero) Tbk's performance was less favorable throughout 2016-2022.